2020
DOI: 10.1038/s41467-020-18595-2
|View full text |Cite
|
Sign up to set email alerts
|

A robust and tunable halogen bond organocatalyzed 2-deoxyglycosylation involving quantum tunneling

Abstract: The development of noncovalent halogen bonding (XB) catalysis is rapidly gaining traction, as isolated reports documented better performance than the well-established hydrogen bonding thiourea catalysis. However, convincing cases allowing XB activation to be competitive in challenging bond formations are lacking. Herein, we report a robust XB catalyzed 2-deoxyglycosylation, featuring a biomimetic reaction network indicative of dynamic XB activation. Benchmarking studies uncovered an improved substrate toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 104 publications
(203 reference statements)
2
29
0
Order By: Relevance
“…The additional control experiment was carried out to show the importance of XB in the present catalysis (Scheme 4). When the reaction was performed in optimal condition with 5 mol% of TBAI (tetrabutylammonium iodide), a halogen‐bond disruptor, [8j] which provided almost no reaction. Based on these observations, a plausible key intermediate structure for the present reaction was constructed and optimised at the M06‐2X/6‐31G(d,p) (def2‐TZVP for iodine) level of theory in toluene within Gaussian 16, with structures generated by GaussView 6 (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…The additional control experiment was carried out to show the importance of XB in the present catalysis (Scheme 4). When the reaction was performed in optimal condition with 5 mol% of TBAI (tetrabutylammonium iodide), a halogen‐bond disruptor, [8j] which provided almost no reaction. Based on these observations, a plausible key intermediate structure for the present reaction was constructed and optimised at the M06‐2X/6‐31G(d,p) (def2‐TZVP for iodine) level of theory in toluene within Gaussian 16, with structures generated by GaussView 6 (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“… Xu et al (2020 ) reported noncovalent halogen bonding (XB) catalyzed α-stereoselective 2-deoxyglycosylation based on d -glycals (IV in Scheme 13 ). This report described the use of noncovalent XB catalyst ( 137 ) for the glycosylation using a variety of d -glycals ( 122 ) of numerous different acceptors which resulted in the corresponding 2-deoxyglycosides ( 124 ) in excellent yields and α-stereoselectivity.…”
Section: Techniques For 12- Cis Glycosylation Reac...mentioning
confidence: 99%
“…A similar type of catalyst (157) was used in the preparation of 2-deoxyglycosides in high α-selectivity from glucals and various glycosyl acceptors. 53 Also, in this case, the use of tetraisopropyldisiloxane as the protecting group in the case of glucals was necessary (Scheme 23). According to the authors, after extensive investigation, a complex reaction network of multiple dynamic interactions is operative.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%